Acute effects of lower-limb intermittent negative pressure on microcirculatory function in Tai Chi athletes: an exploratory study - Wu, Xiaoliang; Li, Lan; Fan, Qianqian (Frontiers in Physiology, 2026)
ObjectiveTo determine whether a single 20-min bout of lower-limb intermittent negative pressure (INP) acutely improves microcirculation in competitive Tai Chi athletes.MethodsTwenty-eight male athletes (20.3 ± 1.0 years) underwent pre- and post-INP assessment of microvascular blood flow, moving blood-cell concentration, velocity, and transcutaneous oxygen (TcPO2) and carbon-dioxide (TcPCO2) tensions at the biceps brachii and vastus lateralis using laser-Doppler flowmetry and gas sensors. Vascular reserve was quantified after 5-min local heating. INP consisted of 30 s at −55 to −60 mbar followed by 10 s at atmospheric pressure for 20 min. Paired t-tests compared pre- and post-values; Cohen’s d gauged effect size.ResultsAt baseline, TcPO2 and TcPO2/TcPCO2 were lower in the lower limb (P < 0.001, d = 0.92–0.75). Post-INP, no significant changes occurred in the upper limb. In the lower limb, TcPO2 increased from 63.9 ± 10.2 to 77.4 ± 10.4 mmHg (P < 0.001, d = 1.31) and TcPO2/TcPCO2 rose from 1.8 ± 0.4 to 2.4 ± 0.7 (P < 0.001, d = 1.05); hemodynamic variables were unchanged.ConclusionOne session of lower-limb INP selectively enhances local oxygenation in Tai Chi athletes without affecting upper-limb microcirculation, offering a rapid, lower-limb-specific recovery strategy.